Estudo do efeito crossover de metanol na reação de redução de oxigênio em células a combustível - (:unkn) unknown (Universidade Federal do Amazonas, 2010)
The direct methanol fuel cells are powers alternatives of energy to do support mainly the batteries. The scientific society come in last decades realizing experiments to overcome the technical barriers that block her commercialization. The effect of methanol crossover, from the anode to the cathode through the membrane, is a very serious problem that that severely reduces the cell voltage, current density, fuel utilization and hence the cell performance. The aim this work is better understand the effect of methanol crossover in this type of technology e try to minimize his negative effects improving the efficiency of fuel cell. To this were prepared electrocatalyts of Pt with an second metal so much in anode as us in cathode using three differents methods: alcohol reduction (MRA), ethylene glycol (MRE) and formic acid (MAF) as reducing agents. The electrodes were prepared following technical of the literature, membrane and electrode assemblies were prepared by pressing an anode and a cathode (Pt onto each side of a Nafion 117 membrane at a pressure of 500 kg cm−2 at 125 ◦C for 180 s. The physical characterization of the electrocatalysts was gone by energy dispersive analysis by X-rays and powder X-ray diffractometer pattern. The effect of methanol crossover was investigate through of electrochemical tests realized in unit cell with PtMo/C and PtRu/C, anode, PtCo/C and PtNi/C, cathode, electrocatalysts. The results showed that alcohol reduction method is better to prepared PtMo/C electrocatalyst, however, its catalytic activity is very lower for methanol oxidation that PtRu/C providing high rate of methanol crossover and reduces cell performance. The results found to the PtCo/C e PtNi/C electrocalysts prepared in this laboratory are approximate the commercials and showed efficient to oxygen reduction reaction and tolerant for methanol oxidation. Thus, we can to affirm that the minimize of effect of methanol crossover lead the increase in cell.
Keywords: Células de metanol; Efeito crossover; Desempenho elétrico; Fuel cells; Effect crossover; Electrochemical performance; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA